2010
DOI: 10.1103/physrevb.81.041102
|View full text |Cite
|
Sign up to set email alerts
|

Theory of quasiparticle interference on the surface of a strong topological insulator

Abstract: Electrons on the surface of a strong topological insulator, such as Bi2Te3 or Bi1−xSbx, form a topologically protected helical liquid whose excitation spectrum contains an odd number of massless Dirac fermions. A theoretical survey and classification is given of the universal features, observable by the ordinary and spin-polarized scanning tunneling spectroscopy, in the interference patterns resulting from the quasiparticle scattering by magnetic and non-magnetic impurities in such a helical liquid. Our result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
103
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 32 publications
4
103
1
Order By: Relevance
“…[12][13][14][15] In Ref. 14, the authors observed that QPI is strongest for the spin LDOS response to magnetic impurities, while the unpolarized LDOS pattern vanishes for magnetic disorder (in the first Born approximation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] In Ref. 14, the authors observed that QPI is strongest for the spin LDOS response to magnetic impurities, while the unpolarized LDOS pattern vanishes for magnetic disorder (in the first Born approximation).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways of analyzing such data. One is to look for quasiparticle interference (QPI) [11][12][13][14][15] in the LDOS Fourier transform. This method is useful for determining short-distance details, and contains similar information as an analysis of LDOS Friedel oscillations in the presence of a single impurity.…”
Section: Introductionmentioning
confidence: 99%
“…Theories have recently been formulated to describe the quasiparticle interference seen in STM experiments, accounting for the absence of backscattering. [70][71][72] Related developments have seen the imaging of a surface bound state using scanning tunneling microscopy. 73 These experimental studies provide evidence of time-reversal symmetry protection of the chiral surface states.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of backscattering was established theoretically early on within a two-dimensional (2D) continuum model for the surface state [4][5][6] and later also confirmed in experiments. [7][8][9] The same 2D surface continuum model finds that, while a local impurity-induced resonance state exists for a potential impurity, its weight diminish as the energy approaches the Dirac point for unitary scatterers and the Dirac point is left unperturbed.…”
mentioning
confidence: 99%